Feminist Stylistic Analysis of Ava Maxâ€™s Song â€œNot Your Barbie Girlâ€ - Manurung, Anna Shinta Vholyna; Perangin-angin, Angelia Maria Igesia; Tanjung, Putri Aziza Muvta; Hasanah, Nurul; Marsha, Siti Azzahra; Rangkuti, Rahmadsyah (Titian: Jurnal Ilmu Humaniora, 2023)
This study analyzes Ava Max's "Not Your Barbie Girl" using a feminist stylistic analysis approach with Sara Millsâ€™ Theory, focusing on its message of women's liberation and rejection of gender stereotypes. The qualitative research focuses on song lyrics and language use, identifying how the song describes women and challenges existing gender constructions. The results suggest that the song adopts a strong feminist perspective, emphasizing self-empowerment, resilience, and rejecting societal constraints. The song disrupts dominant narratives surrounding femininity, positioning women as active agents in their lives. The combination of empowering lyrics and energetic music encourages listeners to embrace their strength and challenge oppressive systems. This study contributes to understanding feminism's expression through popular culture, particularly in music. Abstrak Penelitian ini menganalisis â€œNot Your Barbie Girlâ€ karya Ava Max dengan menggunakan pendekatan analisis stilistika feminis dengan teori Sara Mills, dengan fokus pada pesan kebebasan perempuan dan penolakan terhadap stereotip gender. Penelitian kualitatif berfokus pada lirik lagu dan penggunaan bahasa, mengidentifikasi bagaimana lagu tersebut menggambarkan perempuan dan menantang konstruksi gender yang ada. Hasilnya menunjukkan bahwa lagu tersebut mengadopsi perspektif feminis yang kuat, menekankan pemberdayaan diri, ketahanan, dan menolak batasan sosial. Lagu ini dapat dilihat sebagai narasi dominan seputar feminitas, dan memposisikan perempuan sebagai agen aktif dalam kehidupan mereka. Kombinasi lirik yang memberdayakan dan musik yang energik mendorong pendengar untuk menerima kekuatan mereka dan menantang sistem yang menindas. Penelitian ini berkontribusi untuk memahami ekspresi feminisme melalui budaya populer, khususnya dalam musik.